2012
DOI: 10.4103/2277-9175.100175
|View full text |Cite
|
Sign up to set email alerts
|

Design, formulation and evaluation of nicotine chewing gum

Abstract: Background:Nicotine replacement therapy (NRT) can help smokers to quit smoking. Nicotine chewing gum has attracted the attention from pharmaceutical industries to offer it to consumers as an easily accessible NRT product. However, the bitter taste of such gums may compromise their acceptability by patients. This study was, therefore, designed to develop 2 and 4 mg nicotine chewing gums of pleasant taste, which satisfy the consumers the most.Materials and Methods:Nicotine, sugar, liquid glucose, glycerin, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 14 publications
0
31
0
2
Order By: Relevance
“…In another study, nicotine gum was prepared with equal ratios of these bases, and it had suitable softness and hardness. [17]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, nicotine gum was prepared with equal ratios of these bases, and it had suitable softness and hardness. [17]…”
Section: Discussionmentioning
confidence: 99%
“…In the other study, sweeteners such as sodium saccharine and liquorice had moderate or no effect on masking the bitter taste of nicotine gums respectively, but aspartame showed the strongest effect on modifying the bitter taste of it. [17] Generally for this purpose using the sweetening agents and flavoring agents could help to significantly improve the gum's taste. When we evaluated the effects of the flavoring agents on the organoleptic characteristics of the gums, our results showed that generally the flavoring agents had a softening effect on the formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Крім АФІ, до складу гумок жувальних входять не розчинні у воді основи (еластомери), емульгатори, наповнювачі, воски, антиоксиданти, пластифікатори, підсолоджувачі та смакові добавки [23][24][25].…”
Section: оглядиunclassified
“…Reported in vitro measurements for nicotine gum formulations are much higher; 79-83% release for 18 different formulations (Aslani and Rafiei, 2012) and 80-90% release for 3 formulations during a 1 hour period (Morjaria et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of devices that have been used for testing NRT gums. They have pistons for striking the gum base (Aslani and Rafiei, 2012, Morjaria et al, 2004, Aslani and Rostami, 2015, according to the description of an appropriate apparatus including stainless steel pistons, operation temperature of 37°C and a chewing rate of 60 strikes per minute that is described in the European Pharmacopeia (European Pharmacopoeia, 2010). However, there has not been sufficient data in support of the suitability of this apparatus (Siewert et al, 2003).…”
Section: Introductionmentioning
confidence: 99%